A survey on the (in)security of trusted execution environments - Muñoz-Gallego, Antonio Jesús; Ríos-del-Pozo, Rubén; Román-Castro, Rodrigo; López-Muñoz, Francisco Javier (Elsevier, 2023)
As the number of security and privacy attacks continue to grow around the world, there is an ever increasing need to protect our personal devices. As a matter of fact, more and more manufactures are relying on Trusted Execution Environments (TEEs) to shield their devices. In particular, ARM TrustZone (TZ) is being widely used in numerous embedded devices, especially smartphones, and this technology is the basis for secure solutions both in industry and academia. However, as shown in this paper, TEE is not bullet-proof and it has been successfully attacked numerous times and in very different ways. To raise awareness among potential stakeholders interested in this technology, this paper provides an extensive analysis and categorization of existing vulnerabilities in TEEs and highlights the design flaws that led to them. The presented vulnerabilities, which are not only extracted from existing literature but also from publicly available exploits and databases, are accompanied by some effective countermeasures to reduce the likelihood of new attacks. The paper ends with some appealing challenges and open issues.
Keywords: Seguridad informática; Ordenadores - Medidas de seguridad; Informática - Medidas de seguridad; Computer security; Secure hardware; Trusted execution environments; Hardware attacks; Software attacks; Side-channel attacks